Orchestrated Sex: The Representation of Male and Female Musicians in World-Class Symphony Orchestras - Sergeant, Desmond Charles; Himonides, Evangelos (Frontiers in Psychology, 2019)
This study examines the representation of male and female musicians in world-class symphony orchestras. Personnel of 40 orchestras of three regions, the UK, Europe, and the USA, and distributions of men and women across the four orchestral departments, strings, woodwind, brass, and percussion, are compared. Significant differences in representation between orchestras of the three regions are reported. Practices adopted by orchestras when appointing musicians to vacant positions are reviewed and numbers of males and females appointed to rank-and-file and Section Principals are compared. Career patterns of male and female musicians are also compared. Increases in numbers of women appointed to orchestral posts in the last three decades are compared with increases in the proportion of women in the general workforce. The data of orchestral membership are then compared with the numbers of young people receiving tuition on orchestral instruments retrieved from a large national database (n = 391,000 students). Implications for the future of male and female representation in orchestral personnel are then considered.